5PSQ-124 Medicines and dietary supplements purchased outside the traditional supply chain raise patient safety concerns in hospital and clinical settings. (2nd March 2018) - Fittler, A; Vida, R; Káplár, M; Botz, L
Abstract : Background: The growing market of online pharmacies has caused numerous patient- and medication-safety concerns for health systems. Our previous study in 2013 showed that a high rate of Hungarian hospital patients (8.4%) ordered drugs or dietary supplements online. Purpose: A complex methodology called Risk Based Safety Mapping of Online Pharmaceutical Market has been developed to evaluate patient safety threats. The aim of our current study is to evaluate actual patient safety risks in an outpatient setting and integrate this data into this methodology. Material and methods: A pilot online survey was developed using Google Forms and distributed via social media (Facebook) between 4 October 2017 and 11 October 2017. The target population was Hungarian citizens from the southern Transdanubian region who use outpatient health service for chronic or acute conditions. Three sections were created: demographics, medication and dietary supplement use, and medication and dietary supplement purchase. Results are used to form a questionnaire to collect detailed information in a large (n=1, 000) sample size. Study protocol was approved by the Regional Committee for Research Ethics. Results: The sample of the present study consisted of 111 participants (81 females, 30 males). The mean age of our sample was 28.32 years (SD=10.48). Thirty-one (27.9%) responders reported taking medications regularly and 83 (74.8%) taking medications in acute cases, meanwhile 42 persons (37.8%) use dietary supplements. The participants (95.2%) reported buying the medications exclusively in a pharmacy, three (3, 5%) buying them in a pharmacy or in a store and 1 (1, 1%) to buying medications only on the Internet. Among the participants taking dietary supplements (42), 26 (61.9%) reported buying these products in a pharmacy, 23 (54, 8%) to buying them in a store and 12 (28.6%) to getting them from the Internet. Conclusion: There is a high risk of patients consuming dietary supplements or counterfeit medications purchased over the Internet. This complex methodology can help to identify high-risk patients. Targeted interventions by clinical pharmacists (medication reconciliation, standardised purchasing policies) are the main prevention strategies against the harm caused by health products purchased outside the traditional supply chain. Conflict of interest: Corporate-sponsored research or other substantive relationships: Supported by the UNKP-17–4. New National Excellence Programme of The Ministry Of Human Capacities.